Marketing Government: X-Raying Nigerian Government’s Use of Disinformation in Citizen-Engagement (2015-2023) - Alabi, Soji; Ajibade, Olubunmi; Tommy, Solomon (Journal of Communication and Public Relations, 2024)
The goal of citizen/public engagement is to make develop trust between the government and the governed. However, evidence shows that citizens are losing trust on the government owing to misleading information. Thus, it has become imperative to investigate the underlying aim of government communication and the consequence of the approach adopted by the governments in engaging with their citizens. This paper sought to peripherally investigate the approach adopted by the Nigerian government between May 29th 2015, and May 29th 2023. Since the work of marketing the government is predominately domiciled within the official functions of the Minister of Information and Culture, this paper focuses on the speeches made by the then Minister. The study adopted agenda setting theory and propaganda model as the theoretical framework that guided the research. To attain the basic aim of this paper, qualitative content analysis was adopted by the researcher, which allows for the speeches made by the Minister within the timeframe being studied to be examined. This study found that most of the information and speeches made via interviews, press releases and press conferences for public consumption by the then Minister of on issues about security and economy were generally misleading. Thus, the study recommended that the government adopt a different but balanced approach, as its current strategy will likely cause general disillusionment amongst the citizenry. The balance must keep the citizens gainfully informed, even considering public safety, interest and the government's official secrets.